A Criança Com Síndrome de West na Educação Infantil: Inclusão e Práticas Pedagógicas - Trento, Sabrina da Silva Machado (2020)
This study had the general objective of investigating how the process of including children with West Syndrome occurs in early childhood education. As specific objectives, we sought to know the West Syndrome, its characteristics, particularities and pecul